1986
DOI: 10.1029/jd091id07p07883
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl sulfide concentrations in the surface waters and above the Pacific Ocean

Abstract: We measured the concentration of carbonyl sulfide (OCS) in the marine atmospheric boundary layer and in the surface layer of the equatorial and northern Pacific Ocean on two oceanographic cruises during May and June of 1982 and during March–May of 1983. Our measurements of the mean concentration of atmospheric OCS are 502 ± 21 parts per trillion (ppt) on the 1982 cruise and 511 ± 19 ppt on the 1983 cruise. We found surface water OCS concentrations to range upward from 0.3 STP nL L−1 to a few cases over 3.0 STP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 18 publications
6
44
1
Order By: Relevance
“…They reported an average mixing ratio for COS of 512 k 65 ppt with no significant latitudinal gradient. Very similar results were obtained by Rasmussen et al (1982) and Johnson and Harrison (1986), both of whom found a very constant mixing 13 gradient between the two hemispheres. In particular, they suggested that pollution sources can account for not more that 25% of the total sources of COS both directly and indirectly (as CS2).…”
Section: Atmospheric Distribution Of Cossupporting
confidence: 76%
“…They reported an average mixing ratio for COS of 512 k 65 ppt with no significant latitudinal gradient. Very similar results were obtained by Rasmussen et al (1982) and Johnson and Harrison (1986), both of whom found a very constant mixing 13 gradient between the two hemispheres. In particular, they suggested that pollution sources can account for not more that 25% of the total sources of COS both directly and indirectly (as CS2).…”
Section: Atmospheric Distribution Of Cossupporting
confidence: 76%
“…Known natural sources of COS are oceans (Ferek and Andreae, 1984;Belviso et al, 1986;Johnson and Harrison, 1986), volcanism (Cadle, 1980;Khalil and Rasmussen, 1984;Belviso et al, 1986), precipitation and marshes (Aneja et al, 1979;Steudler and Peterson, 1984) as well as anthropogenic sources such as biomass burning, coal-fired power plants, sulfur recovery, chemical processing and CS 2 conversion (Khalil and Rasmussen, 1984;Crutzen et al, 1985;Bandy et al, 1993;Watts, 2000;Sturges et al, 2001). Besides photolysis and the reactions with OH and O in the stratosphere, vegetation and soils are regarded as the dominating terrestrial sinks (Brown and Bell, 1986;Goldan et al, 1988;Kettle et al, 2002;Sandoval-Soto et al, 2005;Chin and Davis, 1993;Kesselmeier et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This concentration of COS in water was 9.2 pM as calculated as the quotient of an atmospheric concentration of COS of 500 ppt(v) divided by the Henry's law constant of COS in seawater at 20°C of 2.22 [Johnson and Harrison, 1986]. Hence, using equation (1), the flux of COS expected in the absence of COS production when COS-free sweep air is used is --0.18 nmol m"°-h "I.…”
Section: Resultsmentioning
confidence: 99%